Dermatologic manifestation of COVID-19: a systematic review - Alviariza, Annisa; Budiani, Luh M. (International Journal of Research in Dermatology, 2021)
Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infections, causing disease known as COVID-19, has been associated with a myriad of symptoms, including dermatological ones. Despite there has been a consensus on pulmonary and systemic signs and symptoms of COVID-19, the same cannot be said of dermatological ones. We write in attempt to find a common theme of dermatological manifestations of COVID-19. We conducted literature searches from Medline databases as well as Google Scholar using keywords “cutaneous manifestations of COVID-19” and “dermatologic manifestations of COVID-19”. We included case series in our pooled descriptive analysis to describe types of cutaneous eruptions, localizations, and associated symptoms among COVID-19 patients with confirmed real time-polymerase chain reaction (RT-PCR) results. We included 12 case series in our pooled analyses with 2 more analyzed separately due to non-comparable data presentations. The results identified common types of cutaneous eruptions associated with COVID-19 to be maculopapular rash, urticaria, vesicular rash, vascular rash. Eruptions tend to be localized on the trunks, with lesser frequency found on extremities, and eruptions are often accompanied by pruritus of varying intensity. These various eruptions are associated with two distinct pathological pathways, namely inflammation of skin tissues, causing inflammatory rashes, and hypercoagulable state which is associated with vascular rashes. Our literature review identified several common types of cutaneous eruptions associated with COVID-19 with different proposed pathophysiological mechanisms for inflammatory and vascular rashes. This review is limited by its data sources which includes only case series as well as the fact that at this stage in the pandemic, little biomolecular research has been conducted to definitively associate SARS-CoV-2 infection with cutaneous manifestations.